2008
DOI: 10.1016/j.ejcts.2008.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Surgical left atrial appendage occlusion: evaluation of a novel device with magnetic resonance imaging☆

Abstract: We demonstrated a safe, straightforward, persistent and effective method for LAA occlusion with this new LAA clip. MRI effectively demonstrated LAA occlusion and only minor changes in left ventricular volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 14 publications
0
34
0
1
Order By: Relevance
“…In our group of patients, the left atrial appendage was surgically excised in all patients, which may contribute to the improved survival due to the lower risk of thrombo-embolic events [16]. Interestingly, a significant number of our patients remained on coumadin, despite being in sinus rhythm due to other indications.…”
Section: Discussionmentioning
confidence: 98%
“…In our group of patients, the left atrial appendage was surgically excised in all patients, which may contribute to the improved survival due to the lower risk of thrombo-embolic events [16]. Interestingly, a significant number of our patients remained on coumadin, despite being in sinus rhythm due to other indications.…”
Section: Discussionmentioning
confidence: 98%
“…Although stapling techniques are particularly attractive in minimally invasive approaches to AF surgery, this study suggests they are largely ineffective, possibly because the stapler cannot generally be applied down to the true base of the appendage. There is a need for further research into alternative strategies to exclude the left atrial appendage (39); decision making regarding anticoagulation therapy management and the safety of cardioversion in the post-operative setting should not be altered unless an imaging study has confirmed the success of a surgical left atrial appendage closure procedure.…”
Section: Atrial Fibrillationmentioning
confidence: 98%
“…After this, several studies have been published showing the feasibility of this minimally invasive method, most of them using a stapler or a loop snare 31,36,37. One technique has been developed to clip the LAA 38. This device is constructed from two stainless steel strips covered with a knit braided polyester fabric (AtriCure, Inc., West Chester, OH, USA) and can be implanted at the base of the LAA 37,39,40.…”
Section: Current Therapeutic Strategies To Prevent Stroke In Afmentioning
confidence: 99%